G174(P) Audit of care for children with type 2 diabetes mellitus in our service. (24th May 2017) - Seager, E; Karia, S; Trivedi, A; Pattni, S; Fisher, H; Ray, N
Abstract : Aims: Audit of care for children with Type 2 Diabetes Mellitus in our service Methods: Data collected from patient records and results software were audited against current ISPAD and AAP guidelines for investigations and management of children with Type 2 diabetes. Results: 13 children (3 males) diagnosed within the last 4 years were audited. Guidelines were adhered to in 13 (100%) of them. All of them had the required investigations on diagnosis (HbA1c, dyslipidaemia monitoring, renal function, blood pressure and retinopathy screening) and at annual review. All of them were seen by a multidisciplinary team including a Diabetes Clinician, Specialist nurse, Dietician and a psychologist. 10 (76%) were commenced on Metformin within a month of diagnosis. 3 (23%) were controlled on diet only. 3 (23%) of them also had insulin added as adjunct to improve glucose levels and HbA1C. Areas of improvement include discussions surrounding smoking and alcohol which had only been documented for 1 (7%) of these 13 patients. Conclusion: Incidence of type 2 diabetes mellitus is on the rise among children and adolescents. We see a significant cohort in our services likely due to the ethnic groups represented in our population. The Team as well as patients and their carers require regular education and input to maintain good standards of care and prevent future complications. Although this audit found that currently most investigations and management plans are meeting guidelines, there needs to be improvement in targeting specific lifestyle habits around adolescent behaviour. There is a need for reimplementing Community programmes like MEND or other subsidised packages from local authorities to aid in exercise opportunities for weight loss.